2014
DOI: 10.1371/journal.pone.0096362
|View full text |Cite
|
Sign up to set email alerts
|

Association of Relatives of Hemodialysis Patients with Metabolic Syndrome, Albuminuria and Framingham Risk Score

Abstract: Background and AimMetabolic syndrome (MetS), albuminuria, and the Framingham Risk Score (FRS) are significant predictors for cardiovascular disease (CVD). However, the relationship and clinical significance of these CVD predictors in individuals with a family history of end-stage renal disease (ESRD) are unclear. We investigated the association of relatives of hemodialysis (HD) patients with MetS, albuminuria, and the FRS.MethodsOne hundred and sixty-six relatives of HD patients and 374 age- and sex- matched c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Interestingly, a family history of CKD also increased one’s risk of acute renal failure significantly (standardized incidence ratio (SIR) = 1.19) . Furthermore, a recent study suggested that being relatives of haemodialysis patients was independently associated with metabolic syndrome and high cardiovascular risk (defined as ≥10% 10‐year risk of Framingham Risk Score), after adjustment for albuminuria . Therefore, it is reasonable to implement strategies in this high‐risk population for the early detection of kidney disease (both acute and chronic) and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a family history of CKD also increased one’s risk of acute renal failure significantly (standardized incidence ratio (SIR) = 1.19) . Furthermore, a recent study suggested that being relatives of haemodialysis patients was independently associated with metabolic syndrome and high cardiovascular risk (defined as ≥10% 10‐year risk of Framingham Risk Score), after adjustment for albuminuria . Therefore, it is reasonable to implement strategies in this high‐risk population for the early detection of kidney disease (both acute and chronic) and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…12 Furthermore, a recent study suggested that being relatives of haemodialysis patients was independently associated with metabolic syndrome and high cardiovascular risk (defined as ≥10% 10-year risk of Framingham Risk Score), after adjustment for albuminuria. 13 Therefore, it is reasonable to implement strategies in this high-risk population for the early detection of kidney disease (both acute and chronic) and cardiovascular diseases. Urine dipstick, a simple and convenient test, had been used to screen asymptomatic individuals in largescale cohorts; single measurement of proteinuria by dipstick was shown to independently predict risk of ESRD and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…23 In this regard, an increased prevalence of the metabolic syndrome has been observed among relatives of patients with endstage renal disease (ESRD). 24 In our study, apart from age, family history of diabetes was the variable most strongly associated with the metabolic syndrome. All these data are in alignment with the idea that subjects with metabolic syndrome, diabetes and advanced CKD share a common genetic background.…”
Section: Discussionmentioning
confidence: 45%
“…HD patients were reported to have a family history of CKD or ESRD and a higher risk for developing these conditions [24], and the leading cause of death among HD patients is cardiovascular disease [6]. Additionally, the presence of a residual thrombus after the first episode of DVT is an independent risk factor for recurrence [25].…”
Section: Discussionmentioning
confidence: 99%